Vascular measures of atherosclerosis in detrusor overactivity and controls. Issue 8 (14th August 2018) - Ladanchuk, Todd; Kwak, Seojung; Bates, Lucy; Parkin, Katrina; Harris, Katie; Fitzgerald, Oisin; Lynch, William; Moore, Kate H.
Abstract : Aim: The mechanisms leading to the development of detrusor overactivity (DO) are still relatively poorly understood, however, animal studies suggest that atherosclerosis and reduced blood flow to the bladder may be one etiological pathway. Thus, the aim of this study was to evaluate signs of atherosclerosis in a large cohort of women with detrusor overactivity, using two precise measures of atherosclerotic vascular impairment, Ankle Brachial Index (ABI), and Brachial—ankle Pulse Wave Velocity (baPWV). Methods: A prospective cohort study measuring ABI and baPWV of women with DO and controls was conducted. The ABI and baPWV were measured using an automated oscillometric blood pressure machine, to evaluate the degree of atherosclerosis in patients with DO and controls. Associations between ABI and baPWV and important confounding variables were assessed by a linear regression model. Results: Ninety‐eight women with DO, and 98 controls without any symptoms of DO were studied. Multivariate analysis showed an increase in left baPWV of approximately 96 cm/s units of velocity (95%CI 20.65‐172.05, P = 0.01) is predicted significantly by the presence or absence of detrusor overactivity (as well by independent factors of age, diastolic blood pressure and body mass index). A similar effect was seen for right baPWV. Conclusions: On linear regression modeling, the presence of DO was a strong predictor for an increased PWV when controlling for age, BMI and diastolic blood pressure (DBP), thus supporting the hypothesis that atherosclerosis may contribute to the etiology of DO.